THE RISK FACTOR OF ANEMIA IN PREGNANT WOMEN IN THE CLINIC SINGGANI THE CITY OF PALU - Yusria, Yusria; Sakung, Jamaluddin (PROMOTIF: Jurnal Kesehatan Masyarakat, 2016)
ABSTRACTÂ Â The data of WHO (2011), prevalence of anemia in pregnant women in the world of 83,2%. He highest prevalence of anemia found in pregnant women in Africa that is 94,2% and 89,5% in Asia, and 30% in Indonesia. Based on data obtained clinic Singgani, the number of pregnant women in 2015 (January-December) there are 70 people were pregnant women suffering anemia. The Purpose of this study to determine risk factor for incidence of anemia in pregnant women in the clinic Singgani the city Palu. This research is a research survey analitic with the mechanism appoarches Case Control Study. The number of samples which is go respondent with the criteria for inclusion of pregnant women with second pregnancy and axamination Hb. The analysis is used in this study is the analysis of a univariate and bivariate with the test Odds Ratio (OR). The result with the Odds Ratio shows that he was not a risk factor of anemia in pregnant women with OR = 1,000 = 1, Parity is the risk of anemia in pregnant women with OR = 1,496 > 1 and the distance of pregnancy is a risk factor of anemia in pregnant women with OR = 7,818 > 1. The conclusion in this study is the age is not a risk factor of anemia in pregnant women while parity and distance pregnancy are a risk factor of anemia in pregnant women in the clinic Singgani the city of Palu. The advice to the clinic Singgani to further improve outreach and more routine as well as active in the axamination of Hb for any pregnant women.Â Keyword : Age, Parity, Distance Pregnancy, Anemia